Pengembangan Media E-Bactobase Berbasis TASC untuk Melatih Dimensi Bernalar Kritis dan Hasil Belajar Kognitif pada Materi Bakteri Siswa Fase E - Galuh Maharani Putri; Mimien Henie Irawati Al-Mudhar; I Wayan Sumberartha; Deny Setiawan; Mardiana Lelitawati; Sitoresmi Prabaningtyas; Wachidatul Linda Yuhana; Novia Dewi Rahmawati (Universitas Negeri Surabaya, 2026)
Critical reasoning is an essential 21st-century competence and a core pillar of the Profil Pelajar Pancasila. Preliminary analysis at SMA Nasional Malang revealed low levels of students' critical reasoning (59,4%) and cognitive learning outcomes (31,8%). Data indicated 81% of students struggled to understand bacterial concepts perceived as rote memorization, and 63% were unable to analyze related diseases, making bacteria a challenging topic in Phase E. This study aims to develop E-Bactobase, a website-based media integrated with the Thinking Actively in a Social Context (TASC) model, designed to be valid and practical for training critical reasoning and improving cognitive learning outcomes. The media integrates SDGs 3 to equip students with disease prevention knowledge and foster healthy lifestyles. Development followed the Lee & Owens model through analysis, design, and development involving students in classes XIIA and XIIB at SMA Nasional Malang. Data were collected using Likert scale questionnaires and analyzed using percentage conversion based on Aka et al. criteria. Results showed validation scores of 100% (subject matter expert), 99% (media expert), and 97.5% (practitioners). The media was declared practical with an average of 93%. As an implication, this research provides a TASC-based independent learning resource feasible for further efficacy testing in enhancing students' critical reasoning and cognitive learning outcomes.